What Is Massively Parallel Computing, and Why Is It Important? - Hills, W. Daniel (Daedalus: Journal of the American Academy of Arts & Sciences)
Explains what massively parallel computing is and why it is important to understand the effects it will have on life in the near future. Home robots and virtual worlds; Historical importance of Eli Whitney and the invention of the cotton gin; Reference to the fact that massively parallel computers are scalable in that it is always possible to build a more powerful machine by simply adding more processors; Pipelining, functional parallelism, and data parallelism; Description of communication as the most difficult part of parallel computation; More.